Living Qur'an of Pesantren Women: A Manifestation of QS. An-Nisa 34 in A Woman Leadership Role of Nyai Munjidah Wahab - Umniyatul Labibah; Imam Taufiq; Moh. Yasir Alimi (Jurnal Studi Ilmu-ilmu Al-Qur'an dan Hadis, 2022)
This article discusses the study of the living Qur'an of “women’s Pesantren” with a character study approach namely Nyai Munjidah Wahab. So far, women’s Pesantren have been stigmatized as a group of women who only act as “konco wingking”, and their scope of work is only in the domestic or internal area of the pesantren. The leadership of “women’s pesantren” is often considered as a "second class leader" because the main support for pesantren is the kyai or male figure. Nyai Munjidah Wahab gave a different color among the women’s Pesantren in general, by not only becoming the leader of her pesantren but entering the public sphere through organizational and political channels to become a regional head. With the living Qur'an method, this study aims to examine the religious reasoning that frames Nyai Munjidah's behavior on one side and see how Nyai Munjidah Wahab brings QS. An-Nisa: 34 to life in her thoughts and behavior both in her family, Pesantren and in her public leadership. The Living Qur'an of “women’s Pesantren” is analyzed using a gender and cultural perspective. Data collection techniques using observation and interviews. The results of this study indicate that the forms of Nyai Munjidah Wahab's living Qur'an are manifested in several forms of culture, both cognitive and non-cognitive cultures as well as performative and informative cultures that are thick with the values of gender equality. From a cultural perspective, Nyai Munjidah's living Qur'an is a form of active and passive cultural adaptation carried out by Nyai Munjidah Wahab as a “woman’s Pesantren”.